Rising seas could cross thresholds for initiating coastal wetland drowning within decades across much of the United States - Michael J. Osland; Bogdan Chivoiu; James B. Grace; Nicholas M. Enwright; Glenn R. Guntenspergen; Kevin J. Buffington; Karen M. Thorne; Joel A. Carr; William V. Sweet; Brady R. Couvillion (Communications Earth & Environment, 2024)
Abstract Accelerated sea-level rise is an existential threat to coastal wetlands, but the timing and extent of wetland drowning are debated. Recent data syntheses have clarified future relative sea-level rise exposure and sensitivity thresholds for drowning. Here, we integrate these advances to estimate when and where rising sea levels could cross thresholds for initiating wetland drowning across the conterminous United States. Our results show that there is much spatial variation in relative sea-level rise rates, which impacts the potential timing and extent of wetlands crossing thresholds. High rates of relative sea-level rise along wetland-rich parts of the Gulf of Mexico and Atlantic coasts highlight areas where wetlands are already drowning or could begin to drown within decades, including large wetland landscapes within the Mississippi River delta, Greater Everglades, Chesapeake Bay, Texas, Georgia, and the Carolinas. Collectively, our results underscore the need to prepare for transformative coastal change.